2018
DOI: 10.5114/jcb.2018.77955
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiological doses, tumor, and treatment features influence on outcomes after epiescleral brachytherapy. A 20-year retrospective analysis of single-institution: part II

Abstract: PurposeTo assess the influence of the radiobiological doses, tumor, and treatment features on retinopathy, cataracts, retinal detachment, optic neuropathy, vitreous hemorrhage, and neovascular glaucoma at the authors’ institution after brachytherapy for posterior uveal melanoma.Material and methodsMedical records of 243 eyes with uveal melanoma, treated by iodine brachytherapy between 1996 and 2016 at a single center were analyzed. Clinical and radiotherapy data were extracted from a dedicated database. Biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 65 publications
0
18
0
3
Order By: Relevance
“…It is worth to mention that the techniques were used previously at our institution, and there was no difference in either both local tumor control [4] or complications [3,5]. Moreover, for many side effects, the results were better for patients treated at our institution [3,4,5].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It is worth to mention that the techniques were used previously at our institution, and there was no difference in either both local tumor control [4] or complications [3,5]. Moreover, for many side effects, the results were better for patients treated at our institution [3,4,5].…”
Section: Discussionmentioning
confidence: 87%
“…The workflow in choroidal melanoma interventional radiotherapy is typically articulated in five main issues: 1) Multidisciplinary tumor board: case presentation and treatment choice; 2) Treatment planning: plan calculation and preplan approval; 3) Source preparation: applicator loading and sterilization; 4) Surgery: plaque implantation, treatment; 5) Plaque removal [2,3,4,5].…”
Section: Purposementioning
confidence: 99%
“…Brachytherapy has been proven to be very effective and safe way of treatment, providing a good alternative to surgical removal of the eye. In previous studies with a smaller sample of patients, we have reported results in terms of visual acuity outcome [ 28 ], local failure, globe preservation, mortality, local control [ 29 ], and toxicity [ 30 ]. However, there is no gold standard for tumor basal diameter measurement, and these data may be imprecise and impractical in some cases [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Important tumor and treatment features [ 16 , 17 ] as well as the total dose of treatment may influence the outcomes (as reported in literature) of both Iodine-125 [ 18 ] and Ruthenium-106 [ 19 , 20 ]. That is why there is an increasing evidence in literature towards supporting a personalized approach for shaping target-specific dose distributions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%